Pengembangan Lembar Observasi Berbasis Indikator Kinerja untuk Menilai Keaktifan Siswa Melalui Observasi dan Wawancara - Enjelili Rambu Tega Wuasu (Educational Journal, 2026)
Student activeness is a crucial component in the success of the learning process; however, its assessment in practice still faces various challenges due to the absence of structured instruments with clear indicators. This study aims to develop a performance indicator-based observation sheet that teachers can use to assess student activeness objectively and systematically. The study employed a descriptive qualitative approach through observation techniques and in-depth interviews with teachers and students. The findings reveal that teachers' current assessment of student activeness tends to be subjective and inconsistent, relying on general impressions rather than measurable criteria. Based on this needs analysis, an observation sheet was developed incorporating five main indicators of student activeness: participation in discussion, ability to ask questions, ability to answer questions, collaboration in group work, and responsibility in completing assignments. The instrument is complemented by a four-category rating scale (very active, active, fairly active, and less active) to assist teachers in categorizing students' level of activeness. The resulting performance indicator-based observation sheet is expected to serve as an alternative assessment instrument that is more objective, measurable, and sustainable, while also having the potential to enhance students' intrinsic motivation in the learning process..